(3SHc GdPgH aj Yde GdfSHs - (3GHf YfHI , CMeO Hf Ydj Hf MSjf GdOGhOj GdWGdHj GdMSfj, LeGd GdOjf CHh GdYHGS,J (B828 (3g` s
(3ChdgG (B:s
(3hbO cGf QLd Edi HGdTGe efg YgOkG hPeGekG Ydi ONhd HdGOg s
(3BNQgG (B:s
(3aHfbWY GdcdGe MGeOjf Gddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3gcPG hQO GSe GdeDda Ydi GdfSNI hGdUMjM Cf SHc GdPgH dJGL GdOjf GdOjHGU GdMdi GdeJhai (B776 (3JdejP GdYdGeI GdLdi TjN GdSjO CMeO Ydi Hf GdMSjf Hf YfHI eDda (B" (3YeOI GdWdH (B" (3ceG Mbbg UGMH GdPQjYI GfXQ Qbe (B12: 13(3, (B15 338 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B6s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B227 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs